Trädgårdsdesign för hörselskadade - Persson, Bodil (2007)
There is a lot written about being hearing impaired. There are guidelines on how to adjust the indoor environment for the hearing impaired. There is even more written about gardening and garden design from different aspects. However, I found out that there is nothing written about garden design or adjusting the outdoor environment for the hearing impaired. At the background of myself being hearing impaired and garden designer I realised that I actually had adjusted my own garden out of the fact that I am hearing impaired. I wanted to take this one step further. The result is a plan for a garden at a school for hearing-impaired children, the Silvia school in Hässleholm, Sweden. The design and shapes take into consideration that the ones who shall use the garden are hearing-impaired. The garden shall be a peaceful and harmonically place for relaxation and is designed out of the children's needs. Every plant is there for a reason. Every line drawn has a history of thoughts.